2009
DOI: 10.1002/pssc.200982057
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation lifetime data and actual porosity of polymers

Abstract: Application of the three‐component LT9.0 analyses and discrete four‐component PATFIT analysis to PAL distribution in some porous polymers, such as PIM‐1, AF2400, AF1600, PTMSP, give practically the same good fitting. In the conditions of this uncertainty, some additional experiments (thermomechanical tests, NMR on the protons of the absorbed water, thermo‐stimulated luminescence TSL, low temperature gas sorption BET, mathematic molecular‐dynamic simulation) give some arguments in favour of non‐Gaussian distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
(19 reference statements)
4
12
0
Order By: Relevance
“…Their analysis showed that somewhat better correlation with permeability was observed for the RTL parameter a. It confirms the trend reported earlier [80] for polymers with widely varied properties.…”
Section: Pals and Rtl Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…Their analysis showed that somewhat better correlation with permeability was observed for the RTL parameter a. It confirms the trend reported earlier [80] for polymers with widely varied properties.…”
Section: Pals and Rtl Studiessupporting
confidence: 90%
“…It permits one to work with very small samples (up 1-100 mg) in different form (films, fibers, powder, etc.). Recently, it was shown [80] that polymers of different structures having widely varying chain stiffness, free volume and glass transition temperatures reveal different type of emission trend. For polymers with relatively flexible chains (e.g., polyolefins) the main part of emission occurs at low temperatures (below 200 K), while for polymers having much more rigid chains such as amorphous Teflons, poly(trimethylsilyl propyne) etc., the fraction of light emitted in the range 200-380 K is much higher.…”
Section: Positron Annihilation Lifetime Spectroscopy and Radio Thermomentioning
confidence: 99%
“…At low temperatures, intensity of the positronium formation and * corresponding author; e-mail: shant@center.chph.ras.ru integral intensity of TSL are dependent on the storage of the spur electrons (weakly bound electrons). The obtained results make another proof of the spur mechanism of positronium formation [9].…”
Section: Introductionsupporting
confidence: 61%
“…In its turn, the rigidity determines the shape of the curve of the integral intensity of the TSL. The shape is characterized in our case by relative intensity of the high temperature (above 200250 K) component (so-called parameter α) [9].…”
Section: Introductionmentioning
confidence: 99%
“…At a low temperature, the positronium formation rate and the integrated (over wavelength) TSL intensity [14,15] depend on the buildup of weakly bound electrons (track electrons) and are prone to optical quenching (bleaching). These results are another piece of evidence for the spur mechanism of positronium formation [16,17].In [18][19][20], we showed the effectiveness of the combined use of the room temperature PALS and low temperature TSL methods for investigation of some new membrane materials including materials with a heterogeneous structure. The following logic was adopted.…”
mentioning
confidence: 87%